UI/UX Design for School Website Using Design Thinking Method at SMP Negeri 2 Palembang - Aldi Andatu Pradinata (Universitas Mercu Buana Yogyakarta, 2026)
The development of information technology encourages educational institutions to provide digital services that can meet the needs of communication, transparency, and information accessibility. School websites function not only as a medium for conveying academic information, but also as a means of interaction between teachers, students, parents, and the general public. This study aims to design the UI/UX design of the SMP Negeri 2 Palembang website using the Design Thinking method which consists of five stages, namely Empathize, Define, Ideate, Prototype, and Test. This approach was chosen because it is oriented towards user needs and is able to produce innovative, applicable solutions. Data was obtained through interviews, questionnaires, and observations to explore user experiences and problems that arise in using the school website. The analysis results showed problems in aspects of navigation, information accessibility, visual appeal, and website responsiveness to various devices. Based on these findings, a website prototype was designed with the main elements of teacher, student, and admin dashboards, student monitoring features, a learning material repository, an activity gallery, and a more structured announcement system. The trial using the System Usability Scale (SUS) obtained an average score of 89.5 which is included in the